Cryptococcal spondylodiscitis in a non-HIV patient with CD4 lymphocytopenia. Issue 3 (June 2021) - Bhat, Shyamasunder N.; Kundangar, Raghuraj; Ampar, Nishanth; Banerjee, Barnini; Udupa, Chethana Babu K.; Saravu, Kavitha
الملخص: تُعرف العدوى التي تؤثر على الأقراص الفقرية وفقراتها باسم التهاب الفقار وأقراصها. تحدث هذه العدوى عادة عن طريق المكروبات المقيحة، ولا سيما من قبل المكورات العنقودية، والطريق الأكثر شيوعا لانتشارها هو انتشار الدم. وتشمل العدوى غير المقيحة المتفطرة السلية وداء البروسيلات. وتزداد العدوى الفطرية شيوعا مع تزايد عدد اضطرابات نقص المناعة. ومن ضمن العدوى الفطرية عدوى المستخفية. نقدم حالة من هذه العدوى في مريض لا يعاني من نقص المناعة مع تاريخ معروف من العلاج بمضاد السل. حضر رجل يبلغ من العمر ٥٢ عاما إلى مستشفانا يعاني من ألم في الظهر لمدة شهر، وعجز عصبي تدريجي في الأطراف السفلية لمدة أسبوع واحد. وكانت دراساته التصويرية موحية بالتهاب الفقار وأقراصها في مستوى الفقرات الظهرية ١٠-١١ و١١-١٢ مع خراج مجاور للفقرات أيسر. خضع المريض لتخفيف الضغط من الجهة الأمامية الوحشية، والخزعة والاندماج الفقري الخلفي بالأدوات الجراحية. نمت المستخفية من القيح، وأكدت الهيستوباتولوجيا التهاب الفقار وأقراصها بالمستخفية. وعولج المريض بـالأمفوترسين-ب وفلاكونازول عن طريق الوريد. يجب النظر في العدوى الفطرية في التشخيص التفريقي لالتهاب الفقار وأقراصها. Abstract: Infections that affect the intervertebral discs and vertebrae are known as spondylodiscitis. Such infections are commonly caused by pyogenic organisms, particularly Staphylococcus aureus, and hematogenous spread is the most common route. Non-pyogenic infections include Mycobacterium tuberculosis and Brucellosis. Mycotic infections are becoming more common, in line with the growing number of immunodeficiency disorders. Cryptococcus is included among these mycotic infections. We present a case of such an infection in a non-immunocompromised patient with a known history of treatment with antitubercular therapy. A 52-year-old man came to our hospital with a backache of one-month duration and progressive neurological deficits of the lower limbs of one-week duration. His imaging studies were suggestive of spondylodiscitis at the D10–11 and D11–12 levels with a left paraspinal abscess. The patient underwent anterolateral decompression, biopsy, and instrumented posterior spinal fusion. The pus grew Cryptococcus, and histopathology confirmed Cryptococcal spondylodiscitis. The patient was treated with parenteral amphotericin B and fluconazole. A mycotic infection must be considered in the differential diagnosis of infectious spondylodiscitis.